Penilaian Kondisi Jembatan di Kabupaten Sijunjung - Hidayat, Benny; Kamil, Insannul (Jurnal Bangunan, Konstruksi & Desain, 2023)
A bridge is a construction structure whose role is to connect one place to another by crossing a natural or artificial obstacle. Bridge conditions can be caused by many factors such as the influence of weather, traffic loads, the environment, material durability, and so on. Good bridge conditions can be achieved if maintenance is carried out regularly. Therefore, assessing or checking the condition of the bridge is very necessary so that disturbances caused by the factors above can be avoided before an accident occurs. From the results of the field survey, it was found that 52.11% of bridges were in Good condition, 27.46% in Lightly Damaged Condition, 16.90% in Damaged Condition, 2.82% in Severely Damaged Condition and 0.70% in Critical Condition. . The bridge condition assessment was carried out for 2 weeks by carrying out inventory checks, detailed surveys and routine surveys on each bridge.